(untitled) (Ciencias de la Ingeniería y Aplicadas, 2018)
This document describes the excessive rise of the WWW in which the structure of the web is detailed through the different levels or layers that the internet has until reaching the deep internet since each of them has its own characteristics to differentiate them, it has been focused on the differences between the darkweb and surface web with respect to the deepweb both in structure, operation, breadth of information and accessibility, in addition to search strategies that have several resources that at the same time work with the use of special search engines for their access, as is the case of Tor for access to the deepweb, among other search engines with similar characteristics in their operation but each one provides results although they have great benefits in terms of access to non-indexed information and the anonymity of browsing as a great advantage for society but it also gives rise to bad intentions that later become illegal actions of people in certain spaces where everything can be found, such as illegal markets.